THE IMPORTANCE OF THE BLENDED LEARNING SYSTEM IN ORGANIZING THE EDUCATIONAL PROCESS (Academia Science Repository, 2023)
This article examines the concept of Blended learning, its development, its current importance and role, and presents its advantages and disadvantages. Blended learning models are mentioned.